Commissioning and operational results of the 12 GeV helium compression system at JLab. Issue 1 (November 2015) - Knudsen, P; Ganni, V; Dixon, K; Norton, R; Creel, J
Abstract: The new compressor system at Jefferson Lab (JLab) for the 12 GeV upgrade was commissioned in the spring of 2013 and incorporates many design changes, discussed in previous publications, to improve the operational range, efficiency, reliability and maintainability as compared to previous compressor skids used for this application. The 12 GeV helium compression system has five compressors configured with four pressure levels supporting three pressure levels in the new cold box. During compressor commissioning the compressors were operated independent of the cold box over a wide range of process conditions to verify proper performance including adequate cooling and oil removal. Isothermal and volumetric efficiencies over these process conditions for several built-involume ratios were obtained. This paper will discuss the operational envelope results and the modifications/improvements incorporated into the skids.